The Effect Of Taste, Perceived Price And Facilities On Consumer Satisfaction (Survey On Consumers Of Mayasi Café And Resto Asia Plaza Tasikmalaya) - Silvi Agustin; Depy Muhamad Pauzy; Dudu Risana (Penerbit Jurnal Indonesia, 2023)
The purpose of this study was to determine and analyze the effect of taste, perceived price and facilities on customer satisfaction at Mayasi Café and Resto Asia Plaza Tasikmalaya. The research method used is descriptive and quantitative through the causality method with a survey approach to 100 respondents who are consumers of Mayasi Café and Resto Asia Plaza Tasikmalaya. The types of data used are primary data and secondary data. The data analysis method used in this study is multiple linear regression analysis. The test results prove that taste, perceived price and facilities have a significant effect simultaneously or partially on customer satisfaction at Mayasi Café and Resto Asia Plaza Tasikmalaya.